When Are LLMs for Clinical Documentation Considered Medical Devices Under the European Medical Device Regulation (MDR)? (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This article examines how AI systems that assist but do not provide a final diagnosis are classified under the EU Medical Device Regulation (MDR). With the rise of AI in healthcare, especially in managing EHRs and clinical documentation, the paper reconsiders regulatory interpretations in light of new developments. These include the shift from general-purpose LLMs to specialised medical models, like MedGemma, and the 2025 MDCG guidance, which updates classification rules for software. Addressing a gap in current literature, the paper analyses the regulatory status of AI tools participating in the diagnostic process that do not provide the final diagnosis.
Keywords: dispositivo medico; MDCG; MDR AI; documentazione clinica; AI scribe